Identification of novel small molecules that bind to the loop2 region of sclerostin - an in silico computational analysis - Muthusamy, K; Mohan, S; Nagamani, S; Kesavan, C (Physiological research, 2016)
The goal of this study was to identify small molecular weight compounds that bind to sclerostin using in-silico methods because of the established importance of sclerostin-based therapies for the treatment of disease characterized by low bone mass. The zinc database (Zdb) revealed that nine potential molecules bind to the loop2 region (functional site) of sclerostin with ADME/T properties that are within an acceptable range defined for human use. Compounds 30160056 and 56871042 showed the highest docking score. Density functional theory (by HOMO, LUMO and MESP analysis) and MM/GBSA analysis showed that four compounds 30160056, 56871042, 72112226 and 43920281 exhibit high stability among the nine small molecules identified. Induced Docking Fit and Pymol software analyses revealed that the identified compounds differ in the interaction with amino acids in the loop2 region of sclerostin. Six compound exhibited interaction with Ile95 and 2 compounds with Asn93, an amino acid in the loop2 region known to be involved in sclerostin's inhibitory effect, suggesting that the identified compounds have the potential to bind and neutralize sclerostin function. Furthermore, compound 43920281 showed a low risk of toxicity and drug-like characteristic features compared to all nine identified compounds. In conclusion, in silico analysis identified a novel compound 43920281 as a potent anti-sclerostin therapeutic for drug development for the treatment of osteoporosis.
Keywords: Genetic Markers; kostní morfogenetické proteiny; osteoporóza; simulace molekulového dockingu; Bone Morphogenetic Proteins; Osteoporosis; genetické markery; Computer Simulation; Molecular Docking Simulation; počítačová simulace